Anti-poverty effectiveness and efficiency of the guaranteed minimum income programme in Portugal - Rodrigues, Carlos Farinha (2010)
The objective of this paper is to estimate the impact of the Portuguese Guaranteed Minimum Income (GMI) Programme on income distribution and to evaluate its effectiveness and efficiency in fighting situations of poverty and social exclusion. We estimate its impact on the distribution of household incomes and poverty as well as the amount of government expenditure necessary to finance the programme. The simulation shows that 4.8% of domestic households and 5.7% of the population are eligible to receive the GMI. The programme has a small but positive impact on reducing inequality. Similarly, analysis of the effectiveness of the GMI in terms of poverty reduction shows that it has a small but positive impact on the poverty rate. However, the most important consequences of the GMI are sharp gains in the measures of poverty intensity and severity. The efficiency indicators associated with the programme show that 85% of the transfers are awarded to poor people and that 82% of the transfers effectively contributes towards reducing the poverty gap.